Development of Dose Sipping Technology, a New Design Approach for Improving Drug Delivery of Acyclovir in Pediatric Medication - Koshish B. Gabhane1 , Arshiya M. Khan1 , Manish P. Desmukh2 , Ashish B. Budhrani3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: In quest of developing a dosage form having increased focus on the development of noveltechnologies which combines the advantages of liquids as easy swallowing with that of solid dosage formsas storage stability and exact unit dosing as well as taste masking which may improve compliance in childrenor elderly, dose sipping technology tends to be a better alternative and hence preferred for the presentexperimental part.Objectives: The aim and objective of the present work are to study one such new design approach (Dosesipping technology) in order to improve drug delivery of antiviral drugs for pediatric medication.Method: The proposed dose sipping (DS) administration system consists of Acyclovir drug-loaded pelletsformed by the sequential method, further packed in a system of a drinking straw-like tube closed on thebottom end by a filter plug called a controller.Results: Cumulative drug release data for formulated Acyclovir loaded spheres against marketedAcyclovir tablet using Prototype model forstudyingin-vitro drug release per sip, considering the suctionprocess,achieved 99.70 % release within 11 minutes as compared to 60 minutes for 99.45% with improvedpatient compliance.Conclusion: Dose Sipping (DS) Technology is a dosage form which combines the advantages of liquids aseasy swallowing with that of solid dosage forms as storage stability and exact unit dosing as well as tasteselection in the patient favorite beverage might improve compliance in children or elderly